Integration des Klimawandels in langfristige makroökonomische Analysen: Zum Nobelpreis an William D. Nordhaus - Markus Groth (Wirtschaftsdienst, 2018)
Zusammen mit Paul M. Romer erhielt William D. Nordhaus am 10. Dezember 2018 den Schwedischen Reichsbankpreis für Wirtschaftswissenschaften zu Ehren von Alfred Nobel. Nordhaus wurde dabei insbesondere für seine Arbeiten zur Integration zentraler Aspekte des Klimawandels in langfristige makroökonomische Analysen geehrt. – – On December 10, 2018, William D. Nordhaus received the Sveriges Riksbank Prize in Economic Sciences in Memory of Alfred Nobel. Nordhaus was honoured in particular for his work on integrating key aspects of climate change into long-run macroeconomic analysis. Based on fundamental aspects of integrated assessments and taking into account Nordhaus "biographical background, the paper presents key aspects of Nordhaus "integrated assessment models DICE and RICE, discusses the limitations of these models, and addresses both current criticisms on integrated assessment models as well as their relevance for climate policy.
Keywords: H23; O11; Q54; 330